PENINGKATAN KEMAMPUAN MENULIS PUISI SISWA SMK DENGAN MENGGUNAKAN PEMBELAJARAN REFLEKTIF - Anggita, Kiki; Suhendi, Muhammad; Ismayani, Mekar (IKIP Siliwangi, 2018)
Poetry writing skills can cause sensitivity to literary works and stimulate students' brains to think creatively in appreciating literary works. In reality, poetry writing skills are considered difficult by many students. So that the skill of writing poetry on students is still low. For this reason, this study aims to examine and analyze the reflective learning approach to improve students' ability to write poetry in vocational high schools. Population and sample in vocational school student research. This research is made by descriptive method. From the explanation above, it can be concluded that poetry writing skills for vocational students can be improved by using reflective learning. This is known from the number of students who have increased in each cycle. In the first cycle I obtained the results of the first cycle of action test results of language learning on classical poetry writing material score obtained by students cycle I, obtained 14 students reached 46.67% of 30 students earned the value of ≥ 76. This shows the increase in learning skills writing skills enough good. However, there are 16 students reaching 53.33% who can get value <76. While in cycle II, can be seen the result of learning language in classical poetry writing material has reached 83,33% or as many as 25 students from 30 students